Optimalisasi Sistem Kendali PID Pada Pembangkit Listrik Tenaga Surya Untuk Stabilitas Tegangan - Bintang Dwi Cahya; Beni Satria; Hamdani Hamdani (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
This research focuses on optimizing the control system to improve voltage stability in a 10 kW Solar Power Plant (PLTS) located in a tropical region. The main issue addressed is voltage fluctuation caused by the intermittent nature of solar radiation (200–1200 W/m²) and temperature variations (20–50°C), which result in up to 12% overshoot in the inverter. The proposed method implements a Proportional-Integral-Derivative (PID) controller optimized using the Particle Swarm Optimization (PSO) algorithm with real-time irradiation input data. The research integrates a 100 Hz digital low-pass filter to mitigate sensor noise under low irradiation conditions. Simulation results show that the PID-PSO system successfully reduces overshoot from 12.1% to 4.2% under high irradiation, and decreases settling time from 0.62 seconds to 0.31 seconds. The digital filter effectively reduces measurement deviation from 7.2% to 2.8% at 200 W/m² irradiation. The PSO optimization achieved optimal convergence within 37 iterations with an Integral of Time-weighted Absolute Error (ITAE) value of 0.18. This study concludes that the implementation of PID-PSO with a digital filter significantly enhances the voltage stability of the PLTS by 20.3% compared to conventional PID control and is ready to be applied in tropical-region smart grid systems.